Pelatihan Edukasi Gizi Berbasis Komunitas melalui Platform Cookpad Posyandu Desa Jaddih, Kabupaten Bangkalan - Lailatul Muarofah Hanim; M. Masqotul Imam Romadlani; Nur Istiqomah; Imam Sofyan (Yayasan Lentera Avanya Nagari, 2026)
The baby’s growth phase over 6 months of age needs to be supplemented with nutritious complementary foods for toddlers. Proper nutritional intake for toddlers is key to preventing nutritional problems such as stunting. Limited menu variety and access to practical recipes are often obstacles for mothers. Through this training activity, the community services team sought to increase knowledge and skills in preparing nutritious food for toddlers by utilizing the Cookpad digital application. The use of this application also encourages innovation in menus based on locally sourced foods easily accessible as a source of inspiration and a medium for sharing complementary feeding recipes. This community service activity was carried out in Jaddih Village, Socah District, Bangkalan Regency. This training activity adopts a combination of interactive discussions and hands-on practice in creating accounts and searching for recipes using the Cookpad application. This training proved to be effective in increasing the knowledge and skills of mothers and cadres in creating innovative, nutritionally balanced complementary foods from local foods. Participants were not only passive users viewing available recipe options but could also actively add recipes, discuss them online, and upload the results of their recipe innovations accompanied by photos of the dishes they had prepared. The use of the Cookpad application successfully broadened participants' perspectives on the vast array of recipe resources available. It provides the process of preparing complementary foods (MPASI) more varied and memorable. Bayi membutuhkan asupan Makanan Pendamping ASI (MPASI) yang dimulai sejak usia 6 hingga 24 bulan. Asupan makanan bergizi yang tepat merupakan kunci dalam pencegahan masalah gizi seperti stunting. Minimnya pengetahuan tentang variasi menu dan terbatasnya akses terhadap panduan maupun buku resep praktis sering menjadi kendala bagi ibu. Melalui kegiatan pelatihan ini, tim pengabdian kepada masyarakat berupaya untuk meningkatkan wawasan dan keterampilan pengolahan makanan bergizi untuk bayi dengan pemanfaatan aplikasi digital Cookpad. Penggunaan aplikasi ini juga mendorong inovasi menu berbasis pangan lokal yang mudah diakses sebagai sumber inspirasi dan media berbagi resep MPASI. Kegiatan pengabdian masyarakat ini dilaksanakan di Desa Jaddih Kecamatan Socah Kabupaten Bangkalan. Metode yang digunakan adalah kombinasi antara diskusi interaktif dan praktik langsung pembuatan akun serta penelusuran resep menggunakan aplikasi Cookpad. Pelatihan ini terbukti efektif dalam meningkatkan pengetahuan dan keterampilan ibu serta kader dalam membuat inovasi MPASI yang bergizi seimbang dari pangan lokal. Peserta tidak hanya menjadi pengguna pasif untuk melihat pilihan resep yang tersedia, tetapi juga dapat secara aktif menambahkan, berdiskusi secara daring serta mengunggah hasil inovasi resep yang telah dipraktikkan dengan membubuhi gambar hasil masakan. Pemanfaatan aplikasi Cookpad berhasil membuka wawasan peserta terhadap sumber daya resep yang luas, menjadikan proses persiapan MPASI lebih variatif dan berkesan.